Experimental study of the removal of excited state phosphorus atoms by H2O and H2: implications for the formation of PO in stellar winds. Issue 1 (21st June 2022) - Douglas, Kevin M; Gobrecht, David; Plane, John M C
ABSTRACT: The reactions of the low-lying metastable states of atomic phosphorus, P( 2 D) and P( 2 P), with H2 O and H2 were studied by the pulsed laser photolysis at 248 nm of PCl3, combined with laser-induced fluorescence detection of P( 2 D), P( 2 P), and PO. Rate coefficients between 291 and 740 K were measured, along with a yield for the production of PO from P( 2 D or 2 P) + H2 O of (35 ± 15) %. H2 reacts with both excited P states relatively efficiently; physical (i.e. collisional) quenching, rather than chemical reaction to produced PH + H, is shown to be the more likely pathway. A comprehensive phosphorus chemistry network is then developed using a combination of electronic structure theory calculations and a Master Equation treatment of reactions taking place over complex potential energy surfaces. The resulting model shows that at the high temperatures within two stellar radii of a MIRA variable AGB star in oxygen-rich conditions, collisional excitation of ground-state P( 4 S) to P( 2 D), followed by reaction with H2 O, is a significant pathway for producing PO (in addition to the reaction between P( 4 S) and OH). The model also demonstrates that the PN fractional abundance in a steady (non-pulsating) outflow is underpredicted by about 2 orders of magnitude. However, under shocked conditions where sufficient thermal dissociation of N2 occurs at temperatures above 4000 K, the resulting N atoms convert a substantial fraction of PO into PN.